Usefulness of Intra-Aortic Balloon Pump Off Test With Echocardiography for Decision Making in Secondary Ischemic Mitral Regurgitation: A Case Report - Shiokawa, Noriko; Izumo, Masaki; Kuwata, Shingo; Akashi, Yoshihiro J. (Frontiers in Cardiovascular Medicine, 2022)
Our patient was a 60-year-old male with myocardial infarction. Urgent percutaneous coronary intervention was performed with intra-aortic balloon pump (IABP) support. Despite successful revascularization, the patient suffered from cardiogenic shock and heart failure. Secondary mitral regurgitation (MR) was mild and seemed unlikely to be the cause of heart failure. However, when IABP was temporarily stopped (IABP-OFF), secondary MR was aggravated; therefore, we decided to perform transcatheter mitral valve repair. Thereafter, only mild residual MR was observed after IABP removal, and hemodynamic stability was achieved. This case presents IABP-OFF test with echocardiography as a useful method to assess secondary MR.